Optimal condition-based renewable warranty policy for products with three-stage failure process. Issue 2 (3rd March 2020) - Wang, Liying; Yang, Yanmei; Zhu, Huihui; Liu, Guoxin
ABSTRACT: A three-stage failure process divides a product's life into three stages: normal, minor defective and severe defective stages. Under the condition-based renewable warranty policy, inspections are carried out to check which stage the product is in. Condition-based activities, such as shorting inspection intervals, preventive replacement and failure replacement, are carried out properly. From a manufacturer's perspective, the inspection interval is optimized by minimizing the expected cost rate per unit time over the whole warranty coverage. For comparison, the expected cost rate per unit time for warranty models without inspections and with fixed interval inspections are also derived. Numerical examples show that condition-based renewable warranty policy replacement policy can reduce the manufacturer's warranty cost significantly.